The Influence of Remittances on Mutual Transactions in an Isolated Village - Hongsakhone, Soulixay (Journal of Developing Economies, 2019)
In this paper, we investigate the influence of domestic remittances on mutual transactions through the trade of major products among households in an isolated village in a developing country. We use trade data of individual household obtaining from our own Household Survey 2015 and 2016 conducted in northern Lao PDR. By using propensity score matching method, the paper estimates the average treatment effect on the treated, and it finds that remittances have an increasingly significant impact on mutual transactions mainly through increasing in rice, non-timber forest products, and livestock trading among households with remittances. Moreover, this paper also finds that remittances had a more significant contribution to increased stock of goods rather than consumption in households with remittances. Suggesting that households with remittances, which are both consumers and traders, tend to accumulate their resources for future transactions, this is due to external market distance, food insecurity and network constraints. Keywords: Remittance, Developing Country, External Market Distance,Food Insecurity, Network ConstraintJEL Classification: F17, F24, E23